(untitled) (The Review of Diabetic Studies, 2024)
Background: Hospital performance indicators serve as critical benchmarks for assessing care quality, operational efficiency, and patient outcomes. Despite widespread implementation, their effectiveness in improving patient care and satisfaction remains inconsistently documented across healthcare systems globally. Objective: This systematic review synthesizes current evidence on how hospital performance indicators influence patient outcomes and satisfaction levels, while identifying implementation barriers and strategic opportunities. Methods: Following PRISMA guidelines, we systematically searched PubMed, Scopus, Web of Science, and Google Scholar for peer-reviewed studies published between 2015-2024. Search terms included "hospital performance indicators," "clinical outcomes," "patient satisfaction," and "healthcare effectiveness." The ROBIS tool assessed risk of bias. Data extraction focused on indicator types, patient outcomes, satisfaction measures, and implementation challenges. Results: Twenty-eight studies from 15 countries were included, representing diverse healthcare systems and 47,890 patients. Clinical indicators (infection rates, mortality) showed strongest correlation with patient outcomes, with nurse-to-patient ratios demonstrating up to 22% reduction in adverse events. Patient-centered indicators significantly improved satisfaction scores (up to 20% increase) and treatment compliance. Technology-enhanced monitoring systems, particularly AI-driven predictive analytics, showed promising results in reducing mortality rates. Implementation barriers included data inconsistency, staff resistance, and resource limitations. Conclusion: Performance indicators, when strategically implemented with multidimensional approaches, significantly improve both patient outcomes and satisfaction. Success requires integration of clinical, operational, and patient-centered metrics, supported by robust technology infrastructure and organizational commitment. Healthcare institutions should prioritize nurse staffing ratios, infection control measures, and patient experience monitoring as high-impact indicators.